The Influence Of The Forehand Grip On Short Service Ability In Badminton (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the effect of the handle on the short-service ability of badminton games in Penjaskesrek students. This research is a pre-experiment, namely two Group pretest-posttest design, the population in the study were 40 students of Physical Education Class 2022, Makassar State University. The data collection technique uses a short service test instrument, namely the forehand grip service test grip. Based on the data analysis, the results obtained from the pretest average value of the forehand grip ability of 32.3500, the average posttest value of the forehand grip of 52.6000, the value of t count> is 7.818, the significance value of the probability is 0.000, and the t table is 2.818. and the mean value of the backhand grip pre-test ability of 32.1500, the average value of, the significance value of the probability of 0.000, and the t table of 2.746. the value of t table 0.050 is greater than t count 0.025 and the value of sig